Pathomorphological predictors of left heart ventricle dilatation at ischemic cardiomyopathy patients with chronic cardiac decompensation in postoperative period - V. A. Kazakov; M. L. Kozhevnikov (Бюллетень сибирской медицины)
Morphofunctional state of left ventricle (LV) myocardium and right atrial (RA) auricle at 31 ischemic cardiomyopathy patients with chronic cardiac decompensation has been investigated in details. Histological preparations colored with hematoxylin and eosin and by Mallory method have been studied with usual light and polarization microscopy. The correlation of morphofunctional state of ventricle myocardium and atrium has been found, the factors of unfavorable farther results of operational treatment of this patient category have been revealed: presence of morphological myocarditis picture and marked LV myocardium fibrosis were pathomorphological predictors of LV dilatation in late postoperative period.